2004
DOI: 10.1086/383350
|View full text |Cite
|
Sign up to set email alerts
|

Differential Production of Inflammatory Cytokines in Primary Infection with Human Metapneumovirus and with Other Common Respiratory Viruses of Infancy

Abstract: Viral respiratory infections are the most frequent cause of hospital admission for infants and young children during winter. However, the mechanisms of illness that are associated with viral lower-respiratory-tract infection (LRI) are unclear. A widely accepted hypothesis attributes the pathogenesis of viral LRI in infants to the induction of innate inflammatory responses. This theory is supported by studies showing that Toll-like receptor 4 is activated by respiratory syncytial virus (RSV), leading to product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 35 publications
12
125
0
5
Order By: Relevance
“…Later during the infection, a Th2-type IL10 expression and a delayed CTL activity evolved that coincided with persistent virus replication in the lungs of infected animals. These findings are congruent with the earlier finding by Laham et al [11], who observed an attenuated inflammatory response in infected children. In their interesting study on the persistence of HMPV in mice, Hamelin et al [7] found that the persisting viral HMPV RNA was accompanied by a significant ongoing pulmonary inflammation until day 154 post infection, whereas the elevated secretion of mucus was observed only until day 12.…”
Section: Mouse Model (Balb/c)supporting
confidence: 93%
See 2 more Smart Citations
“…Later during the infection, a Th2-type IL10 expression and a delayed CTL activity evolved that coincided with persistent virus replication in the lungs of infected animals. These findings are congruent with the earlier finding by Laham et al [11], who observed an attenuated inflammatory response in infected children. In their interesting study on the persistence of HMPV in mice, Hamelin et al [7] found that the persisting viral HMPV RNA was accompanied by a significant ongoing pulmonary inflammation until day 154 post infection, whereas the elevated secretion of mucus was observed only until day 12.…”
Section: Mouse Model (Balb/c)supporting
confidence: 93%
“…The findings showing that depletion of T cells or NK cells in infected BALB/c mice result in increased virus titers in the lungs are consistent with this hypothesis [1]. These latter data describing the inflammatory response in HMPV-infected mice [2] are consistent with the findings of a recent prospective study that demonstrated much lower levels of respiratory inflammatory cytokines in HMPV-infected infants than in those infected with RSV [11]. The authors suggested that HMPV and RSV either cause disease via different mechanisms or share a common mechanism that is distinct from innate immune activation.…”
Section: Mouse Model (Balb/c)supporting
confidence: 85%
See 1 more Smart Citation
“…144 In contrast, other studies demonstrate that infants undergoing hMPV infection presented lower levels of pro-inflammatory cytokines compare with infants undergoing hRSV or influenza infection, including TNF-a and IL-1b, two cytokines related to the chemotaxis of neutrophils in lungs, as well as IL-12, IL-6 and IL-8. 145 Furthermore, in infants undergoing hMPV infection it was observed that a predominant T H 1 response is generated, since it was detected an increase in the IFN-g/ IL-4 ratio in nasal airway secretions. Taken together, this data indicate that hMPV induces a complex immune response, which might include a mixed T H 1/T H 2 response, similar to what was observed in mice, though further studies are required to evaluate the T cell response in humans upon hMPV infection.…”
Section: Adaptive Immunity Triggered By Hmpvmentioning
confidence: 98%
“…hMPV infection of airway epithelial cells is cytopathic, and the resultant cell injury triggers a series of inflammatory reactions. On the other hand, an unbalanced T helper (Th)1/Th2 immune response to hMPV infection may occur, which would release a series of inflammatory mediators, cytokines, and chemokines, and cause wheezing (21)(22)(23). Studies have shown that TSLP, a newly discovered cytokine, may aggravate excessive The differences between 2 groups were compared using the nonparametric Mann-Whitney 2-sample U test for unpaired data.…”
Section: Discussionmentioning
confidence: 99%